Political Theory and the Displacement of Politics - Honig, Bonnie (Book collections on Project MUSE., 2016)
03 In this book, Bonnie Honig rethinks that established relation between politics and political theory. From liberal to communitarian to republican, political theorists of opposing positions often treat political theory less as an exploration of politics than as a series of devices of its displacement. Honig characterizes Kant, Rawls, and Sandel as virtue theorists of politics, arguing that they rely on principles of right, rationality, community, and law to protect their political theories from the conflict and uncertainty of political reality. Drawing on Nietzsche and Arendt, as well as Machiavelli and Derrida, Honig explores an alternative politics of virtù, which treats the disruptions of political order as valued sites of democratic freedom and individuality.